RISKS ASSOCIATED WITH THE PRESENCE OF ANTIMICROBIAL DRUG RESIDUES IN MEAT PRODUCTS AND PRODUCTS OF ANIMAL SLAUGHTER - D. S. Bataeva; E. V. Zaiko (Теория и практика переработки мяса, 2016)
The risks associated with the presence of antimicrobial drug residues in meat and products of animal slaughter were determined. One of them is the emergence of antimicrobial resistance in pathogenic and conditionally pathogenic microorganisms isolated from meat and products of animal slaughter. It was established that Escherichia coli, Salmonella and Pseudomonas were resistant to ampicillin, tetracycline, tylosin and cephalolexin. However, Listeria monocytogenes did not have resistance to these antibiotics. It was also established that when entering an animal body, antimicrobials were accumulated mostly in liver and kidneys of an animal followed by meat and, to the least degree, in fat. It was found that up to 65% of the tested samples were contaminated with antimicrobials to a greater or lesser degree.